Comparative growth, production, carcass characteristics and reproduction performance of Naked Neck, Black Australorp and their crossbred chicken - Mohammad Alam; Naila Chand; Shabana Naz; Momin Khan; Rifat Ullah Khan; Ibrahim A. Alhidary; Samia Abdelrahman; Marco Ragni (Italian Journal of Animal Science)
This study evaluated the phenotypic and genetic parameters of indigenous Naked Neck (NN), exotic Black Australorp (BA), and their crossbred (NNBA) chickens. A total of 270 day-old chicks (30 per group) were raised under identical conditions from day 1 to 48 weeks of age. Growth performance, including body weight, daily and total gain, feed consumption, and feed conversion ratio (FCR), was highest in BA, followed by NNBA, and lowest in NN. Carcass composition also varied significantly, with BA and NNBA having higher dressing percentages (62.98% and 62.68%, respectively) compared to NN (60.60%). BA produced the heaviest eggs (54.0 g), followed by NNBA (50.9 g) and NN (47.93 g). BA also had the best egg quality, hatchability, and FCR (3.15), with NNBA showing intermediate results. NN had the poorest performance in all traits. Age at sexual maturity was earlier in NNBA (161.23 days) compared to NN and BA. The study concluded that NNBA crossbreds outperformed NN in growth, carcass traits, and egg production, indicating their potential for enhancing rural poultry farming.